Subnatural-linewidth biphotons from a Doppler-broadened hot atomic vapour cell - Chi Shu (Nature Portfolio, 2016)
Quantum-network protocols based on photon-atom interfaces have stimulated a great demand for single-photon sources with narrow bandwidth. Here the authors report the generation of entangled photon pairs with controllable bandwidth and coherence time from a Doppler-broadened hot atomic vapour cell.